(untitled) (JED (Jurnal Etika Demokrasi), 2025)
Social cohesion and patterns of political behavior of the community are often related to the use of religious symbols as a tool to mobilize political interests in the dynamics of democracy in Indonesia. The tendency to visualize religion in politics can be seen in political contestation in the 2024 Indonesian Presidential Election. This phenomenon can cause social polarization and be used as a tool for identity politics. This study aims to analyze the forms of religious visualization in the 2024 Presidential Election in Indonesia. The method used is qualitative research with content analysis with the Norman Fairclough Critical Discourse Analysis approach, namely description, interpretation, and explanation of Instagram social media uploads from three presidential candidates, namely Anies Baswedan, Prabowo Subianto, and Ganjar Pranowo. The results show that the three candidates use religious symbols to build political imagery, with different intensities and approaches used. Anies Baswedan often uses religious rhetoric and Islamic and Christian symbols in his campaigns, Ganjar Pranowo emphasizes interfaith harmony, while Prabowo Subianto tends to display a visualization of nationality and diversity. These findings confirm that social media is a key tool in building a religion-based political narrative, which can contribute to the formation of public perception. This study contributes to the critical literature on politics by providing insights into how identity politics works in the digital realm and its impact on democratic practices in Indonesia.